Meningkatkan Minat Membaca melalui Gerakan Literasi Sekolah - Syahidin, Syahidin (STAI Auliaurrasyidin Tembilahan, 2020)
Literacy will affect the nation's competitiveness in global competition. Literacy skills are very important for the success of individuals and countries at the level of knowledge-based economy in the future global field. This provides reinforcement that the mandatory reading curriculum is applied in Indonesian education. Literacy at SMAN 1 Bunguran North East, Natuna Regency, Riau Islands Province is beneficial for the formation of noble character, fostering a love of reading, stimulating the growth of reading activities outside of school, adding knowledge, and opening up ideas. Literacy is applied in the form of socialization has been carried out to educators, students, to complement reading materials that are already difficult to obtain, presenting digital libraries that are in accordance with the needs of current technological developments. Participants who visit the library will get door prizes, in addition, every two years, there will be announcements about “Duta Baca”. For library development, there are Suggestion Boxes to be filled in by visitors who wish to submit suggestions.